A simple self-adjuvanting biomimetic nanovaccine self-assembled with the conjugate of phospholipids and nucleotides can induce a strong cancer immunotherapeutic effect. (5th October 2020) - Liu, Dan; Liu, Jiale; Ma, Bing; Deng, Bo; Leng, Xigang; Kong, Deling; Liu, Lanxia
Abstract : The biomimetic nanovaccines not only promoted antigens endocytosis into dendritic cells via receptor-mediated pathways but also induced antigens cross-presentation eliciting CD8 + T-cell responses. CPG-ODN as an adjuvant further enhanced the anti-tumor immune responses. Abstract : Biomimetic nanoparticles have potential applications in many fields due to their favorable properties. Here, we developed a self-adjuvanting biomimetic anti-tumor nanovaccine, which was self-assembled with an amphiphilic conjugate synthesized with the phospholipids of 1, 2-dioleoyl- sn-glycero -3-phosphoethanolamine (DOPE) and hydrophilic Toll-like receptor (TLR9) agonist CpG ODN. The nanovaccine could not only provide effective initial antigen stimulation and sustained long-term antigen supply with a controlled release, but also induce antigen cross-presentation via the MHC-I pathway initiating CD8 + T-cell responses. Moreover, the dense nucleotide shell around the nanovaccine could promote antigen endocytosis via various receptor-mediated pathways into dendritic cells. CpG ODN interacted with TLR9 triggering the cytokine secretion of TNF-α and IL-10, which further boosted the anti-tumor humoral and cellular immune responses, which led to a significant tumor suppressive effect and remarkable survival prolongation. So, this nanovaccine self-assembled with phospholipid–nucleotide amphiphiles can serve as a safe, simple and efficient approach for anti-tumor immunotherapy.